Increasing Knowledge of Law Students of UMN Al-Washliyah Medan on Visum Et Repertum - Sembiring, Asan Petrus; Sembiring, Erwin; Malau, Oktafianna; Rahmadsyah; Rival, Adrian; Aprialdi, Hendra (Talenta Publisher, 2023)
In the process of investigating cases involving the life of a person, investigators generally ask for help from experts, such as doctors in the form of information called visum et repertum. Good cooperation between the police/investigators and doctors/forensic experts has been established for a long time and continues to work hand in hand to enforce justice for both victims and suspects. Often peace or amicable settlements are unsuccessful, while evidence has been lost due to the healing process. So that at this time when a visa is requested, the results of the examination are not in accordance with the actual crime so that the victim will be disappointed with the court's decision. The role of the investigator is very much expected to explain the intent and purpose of the victim's examination by the doctor to make a visum et repertum so that the public will understand the importance of the Visum et Repertum which is valid evidence. Therefore, socialization is needed in the form of counseling with the topic of visum et repertum. The activity was carried out on FH UMN Al-Washliyah students with lecture and question and answer methods, then an evaluation of success will be carried out with a pre-test before counseling and post-test after counseling. The activity was attended by 118 people with the results of the pre-test (mean score of 61), and post-test (mean value of 82), which means that there was an increase in students' understanding of the visum et repertum after counseling.